SIFAT FISIKA TANAH DAN PRODUKSI KEDELAI (Glycine max (L) Merril) DI PERKEBUNAN KELAPA SAWIT AKIBAT PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT - Suryani '; Nelvia '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Soybean contains high protein that the yield can be increased as intercrops in oil palm plantation. The purpose of this research was to study the application of compost of oil palm empty fruit bunches (OPEFB) to physical characteristic and production of soybean as intercrops among in oil palm plantation. The research was conducted in oil palm plantation, Faculty of Agriculture, University of Riau from February to May 2014. The resecarch carried out experiments used a randomized block design, as treatment is the application of compost of OPEFB that consist of 4 levels (0, 5, 10 and 15 tons/ha), each of treatment repeated 3 times. The effect of each treatment was known Duncan's New Multiple Range Test (DNMRT) at 5% level. The result of this research showed that the application of compost of OPEFB with a dose of 5, 10 and 15 tons/ha effected to physical characteristic of soil such as: expedite permeability, increase the water content and the infiltration rate, but not effected to the bulk density and pore space total. The application of compost of OPEFB 5 tons/ha increase the number of pods, pod percentage pithy, weight of 100 seeds and yield per plot are not significant compared with without compost. The increase the dose of compost of OPEFB to 10 to 15 tons/ha has no effected on all parameter. Keywords: Soybean, compost of oil palm empity fruit bunches, physical characteristic of soil